Investigating Impacts of Spatial Configurations on Collaborative Writing - Gonzalez-Ibanez, R (First Monday, 2015)
Collaboratively seeking and constructing information is becoming an increasingly important activity in our lives. Yet, many important aspects of such common undertakings are still understudied or unclear, including the effect of spatial configuration in information synthesis or writing process. This article investigates the effects of location-based setups on collaborative writing in the context of information seeking. These investigations are done using a laboratory study and an experimental system for collaboratively seeking and synthesizing information. A total of 30 pairs (60 subjects) were randomly assigned to one of the three experimental conditions: (1) on a single shared workstation; (2) in the same room with individual computers; and, (3) remotely located with text chat. By analyzing the way the collaborative pairs constructed their reports, it was found that those remotely located spent less effort per edit than those in the same room. Separate location discouraged social interactions and boosted the writing efficiency. These differences in various measures across different configurations, as discovered through exploratory analysis - both qualitative and quantitative - provide useful guidelines for developing collaborative systems, specifically presenting trade-offs among communication efforts, social interactions, and productivity. The work reported in this paper is a first known attempt to investigate impacts of spatial configuration on collaborative writing in the context of information seeking. In doing so, it brings together, and benefits to, scholarly inquiries from computer-supported cooperative work (CSCW) and library and information science (LIS) fields. © First Monday, 1995-2016.